Investors’ perception towards Investment In securities with special reference to Salem district - Monika T; Dr. S. Devi; Dr. V. Santhi (Journal of Contemporary Research in Management (JCRM), 2024)
The purpose of this study, "Investors’ Perception towards Investment in Securities with Special Reference to Salem District," is to pinpoint the major variables influencing investors’ ability to make the best possible investment choices. It assesses the level of investor awareness in choosing suitable investment options, including mutual funds, stocks, bonds, and other financial products. Examining how investors perceive the management of their investment portfolios, taking into account factors like financial objectives, time horizon, and diversification, is one of the main goals. The study also evaluates investors’ comprehension of how to balance risk and return, which is a crucial component of long-term wealth creation and successful investment planning. Using primary data gathered from investors in the Salem district via questionnaires and interviews, a systematic methodology is used. It is anticipated that the results will highlight financial literacy gaps as well as the impact of demographic variables like age, income, and education on investment choices. The study also looks at the patterns of behavior that influence the preferences and decisions of investors. Financial advisors, legislators, and academic institutions will be able to create better investment advice programs and awareness campaigns with the aid of these insights. The study ultimately advances a more comprehensive knowledge of investor psychology and behavior in semi-urban areas such as Salem, encouraging more knowledgeable, well-rounded, and logical financial investment strategies.